Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
X2x—7=15
2x=15+7
2x=22
x=22:2
x=11
4x +5=205
4x=205–5
4x=200
x=200:4
x=50
80/(x+1)=40
==> 80: x+1=40
80:x=40-1
80:x=39
x=80:39
x=80/39
72–(2x—4)=2
2x—4=72-2
2x—4=70
2x=70+4
2x=74
x=74:2
x=37
75-5(x+3)=5
5(x+3)=75–5
5(x+3)=70
x+3=70:5
x+3=14
x=14–3
x=11
7x:7=4
7x=4.7
7x=28
x=28:7
x=4
20:(x—5)=20
x—5=20:20
x—5=1
x=1+5
x=6
9(2x—8)=0
2x=0:9
2x=0
x=0:2
x=0
2080:4x=40
4x=2080:40
4x=52
x=52:4
x=13
1) x - 2 = -6
x = -6 + 2
x = -4
2) -5 . x - ( -3 ) =13
-5 . x = 13 + ( -3 )
-5 . x = 10
x = 10 : ( -5 )
x = -2
bài 1
a) \(15+\left(32-2x\right)=65\)
\(32-2x=65-15\)
\(32-2x=50\)
\(2x=32-50\)
\(2x=-18\)
\(x=-18:2\)
\(x=-9\)
vậy \(x=-9\)
b)\(18.\left(x-5\right)^2=72\)
\(\left(x-5\right)^2=72:18\)
\(\left(x-5\right)^2=4=2^2\)
\(x-5=2\)
\(x=2+5=7\)
vậy \(x=7\)
c)\(\left|19-x\right|-6=0\)
\(\left|19-x\right|=0+6=6\)
\(19-x=\pm6\)
\(\left[{}\begin{matrix}19-x=6\\19-x=-6\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=13\\x=25\end{matrix}\right.\)
vậy \(x\in\left\{13;25\right\}\)